Cartografias poéticas : trajetórias meio a arte e a cultura visual - Victorio Filho, Aldo (2019)
We present in this article part of the conditions by which we developed our research on the teaching of the Visual Arts, in the city of Rio de Janeiro, with the work of cartographies of teaching and learning processes, emphasizing their poetic exploration as indispensable for the deepening of the investigative experience. In this sense, we offer an outline of each one of the workshops that allowed us to start the research work, in a simultaneous process of cartographic elaboration and production between the spaces of the university and the college studied